Effects of Luteolin Treatment on Postharvest Quality and Antioxidant Capacity of Nanfeng Tangerines - Wenjuan Dong; Xiaohan Wang; Miaolian Xiang; Jinyin Chen; Jiaoke Zeng; Ming Chen (Foods)
Postharvest quality deterioration is a major factor affecting the economic value and marketing of Nanfeng tangerines. The objective of this study was to explore the effects of luteolin treatment on the postharvest quality and antioxidant capacity of Nanfeng tangerines. We applied 1 g/L and 3 g/L luteolin to fruit after harvest and evaluated the decay rate, postharvest quality, and antioxidant capacity during a 60-day storage period at room temperature. The results indicated that, compared to untreated fruit, Nanfeng tangerines treated with 3 g/L luteolin exhibited enhanced appearance and flavor quality, as well as delayed disease incidence, during room-temperature storage. Additionally, flavor quality analysis revealed that luteolin treatment maintained high levels of titratable acid (TA) by delaying the degradation of organic acids such as citric, tartaric, succinic, ascorbic, and oxalic acids. Furthermore, luteolin treatment inhibited malondialdehyde (MDA) and H2O2 accumulation by enhancing the content of total phenols and flavonoids content, augmenting antioxidant enzyme activities (peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD)), and elevating the overall antioxidant capacity measured through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging rate. Collectively, these results demonstrate that luteolin has potential as a preservative for promoting postharvest quality and antioxidant capacity. Additionally, our findings elucidate the mechanisms by which plant-derived flavonoids contribute to the preservation of freshness.